2023
DOI: 10.1002/ctm2.1197
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of targeting minimal residual disease in melanoma

Abstract: We demonstrate that melanoma responds to targeted therapies (TTs) and immune checkpoint inhibitors (ICIs) in three phases: early response, minimal residual disease (MRD) and disease progression.• The minimal residual disease of both TT and ICI is a nidus for the development of therapeutic resistance and, thus, warrants additional characterization of both tumour cells and their surrounding tumour immune microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Phenotype switching has been linked to drug resistance, with the undifferentiated/invasive cell state recently found to be drug tolerant 8,13,72 .This finding has important clinical relevance, as drug tolerant persister cells are a major contributor to relapse in patients 73 . Based on this, we examined how the confined, invasive state affects response to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotype switching has been linked to drug resistance, with the undifferentiated/invasive cell state recently found to be drug tolerant 8,13,72 .This finding has important clinical relevance, as drug tolerant persister cells are a major contributor to relapse in patients 73 . Based on this, we examined how the confined, invasive state affects response to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As a common skin tumor, cutaneous melanoma (SKCM) has a poor prognosis and are more likely to present with aggressive clinical manifestations such as ulcers 1 . Recent clinical trials have shown that immune checkpoint inhibitors and BRAF/MEK inhibitors significantly improve overall survival in patients with advanced melanoma, but there are still melanoma patients who could not benefit from these methods since poor immune response to tumors and low rates of BRAF gene mutations 2–4 . It is still of great significance to find specific tumor markers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%